2021
DOI: 10.3390/en14144279
|View full text |Cite
|
Sign up to set email alerts
|

A Consensus Algorithm for Multi-Objective Battery Balancing

Abstract: Batteries stacks are made of cells in certain series-parallel arrangements. Unfortunately, cell performance degrades over time in terms of capacity, internal resistance, or self-discharge rate. In addition, degradation rates are heterogeneous, leading to cell-to-cell variations. Balancing systems can be used to equalize those differences. Dissipative or non-dissipative systems, so-called passive or active balancing, can be used to equalize either voltage at end-of-charge, or state-of-charge (SOC) at all times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This subsection gives an overview of experiments measuring the specific heat capacity of the entire stack 𝑐 𝑠𝑡𝑎𝑐𝑘 and compares the results with the two previous subsections. According to Equation (7), 𝑐 𝑠𝑡𝑎𝑐𝑘 depends heavily on the mass fractions of the stack components, which are listed in Table 4 for some lithium-ion cells based on the total cell mass 𝑚 𝑐𝑒𝑙𝑙 .…”
Section: Heat Capacity Of Electrode-separator Stacksmentioning
confidence: 99%
See 1 more Smart Citation
“…This subsection gives an overview of experiments measuring the specific heat capacity of the entire stack 𝑐 𝑠𝑡𝑎𝑐𝑘 and compares the results with the two previous subsections. According to Equation (7), 𝑐 𝑠𝑡𝑎𝑐𝑘 depends heavily on the mass fractions of the stack components, which are listed in Table 4 for some lithium-ion cells based on the total cell mass 𝑚 𝑐𝑒𝑙𝑙 .…”
Section: Heat Capacity Of Electrode-separator Stacksmentioning
confidence: 99%
“…For example, Kraft et al [6] observed that cells with a high-capacity cathode active material (lithium and manganese-rich) released up to four times as much heat during discharges compared to cells with a commonly used cathode active material (nickel-rich). On the other hand, Barreras et al [7] showed that the problem of non-uniform temperatures during EV fast charging can be solved with innovative balancing concepts, but at the expense of additional cost and complexity, and the cooling needs are still significant. Indeed, temperature is an important battery state that affects energy efficiency [8],…”
Section: Introductionmentioning
confidence: 99%
“…Proof: First, let us denote the set of feasible points for the relaxed problems as F = ({x, y, u, w} | (7b) − (7h) hold) (11) and let us denote the set of feasible points for the original problem as…”
Section: Distributed Feasibilitymentioning
confidence: 99%
“…Although prolonging range is seemingly one of the key abilities of active cell balancing [10], this benefit is only actively aimed for in [8] and [7]. Moreover, having acknowledged violation of the voltage limit as the key indicator for stopping current flow, it is important to see that literature often applies inaccurate battery models [3], i.e., without dynamical overpotential dynamics and with linear open-circuit voltage relations [11]. In previous work of Hoekstra et al [12], [13], range maximization has been posed as the sole objective of active cell balancing.…”
Section: Introductionmentioning
confidence: 99%
“…First, Barreras, J.V. et al [1] present novel research on the distributed multi-objective control algorithm, which is based on a multi-agent consensus algorithm. The authors implemented and validated the control in simulations, considering an electro-thermal lithium-ion battery model and an electric vehicle model parameterized with experimental data.…”
Section: Special Issue Contentmentioning
confidence: 99%